A Preference-Sensitive Online Instrument to Support Shared Decision Making for Patients With Pelvic Organ Prolapse: A Pilot Multicenter Randomized Controlled Trial. Issue 11 (November 2021) - Hulbaek, Mette; Primdahl, Jette; Birkelund, Regner; Al-kozai, Selwan Adnan Hussein; Barawi, Sabat; Ebbesen, Niels Teglhus; Nielsen, Jesper Bo
Abstract : A preference-sensitive instrument for women with pelvic organ prolapse was developed to increase shared decision-making. This study aimed to assess the feasibility of a randomized controlled trial to measure the effectiveness of the instrument. A pilot randomized controlled trial was conducted at three Danish gynecological clinics to assess feasibility through recruitment rates, per-protocol use and women's perception of (1) support for decision-making, (2) shared decision-making (Shared Decision-Making Questionnaire), and (3) satisfaction with their decisions. In addition, a focus group interview with participating gynecologists (five gynecologists) was conducted. We invited 226 women and recruited 46 (20%). The most common reason (45%) for nonparticipation was overlooking the invitation in their online public mailbox. Shared Decision-Making Questionnaire showed high data completeness (96%) but indicated a ceiling effect. Women felt the developed instrument supported their decision-making and more so if it was used interactively during consultations. Despite finding the instrument generally useful, gynecologists tended to apply the instrument inconsistently and not per protocol (41%), and some used it as a template for all consultations. This pilot study indicates that recruitment methods, for a future randomized controlled trial, for example, nurse-led preconsultations, need reconsideration due to low recruitment rates and inefficient per-protocol use. In a future randomized controlled trial, cluster randomization should avoid the carryover effect bias.